The potential of wastewater monitoring as a novel surveillance tool for early warning of Bordetella pertussis outbreaks - Songzhe Fu; Xin Du; Zheng Xu; Haifeng Li; Hui Yao; Shuyue Tang; Wenjuan Zhao; Min Hao; Zhiguang Qiu; Zengguo Wang (Emerging Microbes and Infections)
The prolonged latency period and delayed reporting of clinical surveillance data have led to a sluggish response to Bordetella pertussis outbreaks in China. Wastewater-based surveillance (WBS) provides real-time, cost-effective monitoring of various viruses. To confirm whether this approach can be applied to B. pertussis, 271 patients infected with B. pertussis were enrolled to evaluate the fecal shedding patterns of the bacterium. Concurrently, we collected wastewater samples in a typical northern (Xi’an) and southern city (Nanchang) in China, from September 2023 to July 2024. The concentrations of B. pertussis in the sewage were detected using quantitative polymerase chain reaction (qPCR). Additionally, metagenomic sequencing with pre-enrichment was employed to trace genotypes of B. pertussis. We report that 40.2% of cases tested positive for B. pertussis in fecal samples. Sewage surveillance identified two waves of B. pertussis infection in Xi’an and one wave of B. pertussis outbreak in Nanchang. The concentration of B. pertussis in sewage showed a strong correlation with the dynamics of diagnosed cases. Notably, each peak of sewage B. pertussis concentration occurred 10 days prior to clinical surveillance, underscoring the value of WBS in early warning. Additionally, both clinical and wastewater surveillance demonstrated consistency in the prevalence estimation of B. pertussis infection cases. Finally, relative to clinical surveillance, wastewater sequencing also revealed the same genotypes of B. pertussis. This study presents the first comprehensive analysis of the fecal shedding of B. pertussis, thereby establishing the potential for early detection of B. pertussis outbreaks through WBS.